Electrochemical sensing of fentanyl as an anesthesia drug on NiO nanodisks combined with the carbon nanotube-modified electrode - Li, Xi; Luo, Bo; Liao, Min; Mohamed, Abdullah (Frontiers in Chemistry, 2022)
Fentanyl was successfully determined in the current effort based on hexagonal NiO nanodisks (HG-NiO-NDs) fabricated by hydrothermal protocol. The synergism of HG-NiO-NDs with multiwall carbon nanotubes (MWCNT), large specific surface area and active material enabled the electrochemical sensor to show potent electrochemical behavior. Admirable performance was found for the fentanyl measurement by MWCNT and HG-NiO-NDs-modified pencil graphite electrode (MWCNT/HG-NiO-ND/PGE). The correlation of oxidation currents with the pH value, concentration and sweep rate of supporting electrolyte were determined for the optimization of conditions to detect the fentanyl. The surfaces of modified and unmodified electrodes were characterized as well. The diffusion-control processes were confirmed on the basis of anodic peak findings. The results also revealed a two-electron transfer process. The linear range was obtained to be 0.01-800.0 μM for the fentanyl concentrations on the developed electrode, with the sensitivity of 0.1044 μA/mM/cm2. The limit of detection (S/N=3) was 6.7 nM. The results indicated the ability of the modified electrode to fabricate non-enzymatic fentanyl sensor applications.